In vitro interactions between farnesol and fluconazole, amphotericin B or micafungin against Candida albicans biofilms. (6th October 2014) - Katragkou, Aspasia; McCarthy, Matthew; Alexander, Elizabeth L.; Antachopoulos, Charalampos; Meletiadis, Joseph; Jabra-Rizk, Mary Ann; Petraitis, Vidmantas; Roilides, Emmanuel; Walsh, Thomas J.
Abstract : Objectives: Biofilm formation by Candida albicans poses an important therapeutic challenge in human diseases. Typically, conventional antifungal agents encounter difficulty in treating and fully eradicating biofilm-related infections. Novel therapeutic approaches are needed to treat recalcitrant Candida biofilms. Farnesol is a quorum-sensing molecule, which induces apoptosis, inhibits Ras protein pathways and profoundly affects the morphogenesis of C. albicans . We therefore investigated the interactions between farnesol and different classes of antifungal agents. Methods: The combined antifungal effects of triazoles (fluconazole), polyenes (amphotericin B) and echinocandins (micafungin) with farnesol against C. albicans biofilms were assessed in vitro . Antifungal activity was determined by the XTT metabolic assay and confocal microscopy. The nature and the intensity of the interactions were assessed using the Loewe additivity model [fractional inhibitory concentration (FIC) index] and the Bliss independence (BI) model. Results: Significant synergy was found between each of the three antifungal agents and farnesol, while antagonism was not observed for any of the combinations tested. The greatest synergistic effect was found with the farnesol/micafungin combination, for which the BI-based model showed the observed effects as being 39%–52% higher than expected if the drugs had been acting independently. The FIC indices ranged from 0.49 to 0.79, indicating synergism for farnesol/micafungin and farnesol/fluconazole and no interaction for farnesol/amphotericin B. Structural changes in the biofilm correlated well with the efficacies of these combinations. The maximum combined effect was dependent on the farnesol concentration for micafungin and amphotericin B. Conclusions: Farnesol exerts a synergistic or additive interaction with micafungin, fluconazole and amphotericin B against C. albicans biofilms, thus warranting further in vivo study.